Performance of broiler chicken fed physically and chemically treated jatropha (Jatropha curcas) seed meal - Tiurma Pasaribu; E. Wina; B. Tangendjaja; S. Iskandar (Indonesian Center for Animal Research and Development (ICARD), 2009)
Jatropha seed meal which is a by-product of biofuel is rich in protein. Its utilization as feed ingredient is limited by the presence of several anti nutritive and toxic compounds. An experiment was conducted at the Indonesian Research Institute for Animal Production to evaluate the effect of jatropha seed meal on broiler performance. Jatropha seed meals were treated physically, chemically or their combination to reduce or eliminate the anti nutritive and toxic compounds. Then, the inclusion of untreated or treated jatropha seed meals in the diet at the level of 4% was evaluated on broiler. The experiment was done in Completely Randomized Design with 5 treatments of feed, i.e 1) control feed, 2) feed containing untreated jatropha seed meal (OO), 3) feed containing physically treated jatropha seed meal (OTO), 4) feed containing chemically treated jatropha seed meal (EHM) and 5) feed containing physically and chemically treated jatropha seed meal (EHMO). Every treatment had 7 replications with 5 chickens for each replication. The treatment diets were given to 7 days old chicken for 14 days. The observed parameter were feed intake, daily gain, feed conversion ratio, and mortality. The broiler performance recieved EHMO feed was better that those of OTO or EHM treatment (751.1; 731.2; 498.8 g of body weight for EHMO, EHM and OTO treatments, respectively), however, it was lower than the control treatment (856.3 g). Feed Conversion Ratios of EHM and EHMO treatments were not significantly different from control treatment (1.868; 1.813 vs 1.707), however, they lower than OO (2.532) and OTO (2.249) treatments. Chicken mortality of EHMO treatment was much lower than OO that of treatment (0 vs 34.29%, respectively). In conclusion, the processing technology of jatropha seed meal using combined physical and chemical treatments (EHMO) was the best choice as it gave better chicken performance without mortality compared to other techniques in this experiment. Key words: Jatropha Seed Meal, Detoxification, Broiler Chicken, Performance